2010
DOI: 10.3164/jcbn.10-16gfr
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin and oxidative stress in gastrointestinal tract

Abstract: Oxidative stress is a major cause of the gastrointestinal damage under physical or psychological stress. Ghrelin exhibits gastroprotective effects and they are supposed to be derived from antioxidant effects. In gastroduodenal mucosal injury, the plasma ghrelin levels increase in response to the demand for gastroduodenal cytoprotection. However, in the condition of Helicobacter pylori-induced gastric mucosal severe atrophy, the plasma ghrelin concentration shifted to lower levels. In diabetic gastroparesis, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 54 publications
(56 reference statements)
4
50
0
1
Order By: Relevance
“…The pathophysiological interactions between H. pylori and the brain-gut axis likely involve ( Figure 1): (1) axon injury or stimulation (neuroinflammation) by bacterial cytotoxins (VacA) [60,72,78] , neutrophil-attractant chemokine IL-8 [79] , and/or neutrophil-activating protein (H. pylori-NAP) [75,79] ; (2) axon damage or stimulation by autoimmunological reactions due to mimicry of VacA, bacterial aquaporin (AQP), H. pylori-NAP and human antigens [51,53,79,80] ; (3) H. pylori-induced production of free radicals [80][81][82] , cytotoxins and cytokines [57][58][59][60][61]78] , which may also result in blood-brain barrier disruption; (4) changes in neurotransmitter secretion in gastric mucosa and spinal cord [56,72,75,81,[83][84][85] ; (5) neuron injury resulting from gastric mucosa atrophy and a decrease in vitamin B12 absorption [86] ; and (6) changes in stomach and intestinal microbiota [6,[87][88][89] .…”
Section: Role Of the Brain-gut Axis In Acute H Pylori Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiological interactions between H. pylori and the brain-gut axis likely involve ( Figure 1): (1) axon injury or stimulation (neuroinflammation) by bacterial cytotoxins (VacA) [60,72,78] , neutrophil-attractant chemokine IL-8 [79] , and/or neutrophil-activating protein (H. pylori-NAP) [75,79] ; (2) axon damage or stimulation by autoimmunological reactions due to mimicry of VacA, bacterial aquaporin (AQP), H. pylori-NAP and human antigens [51,53,79,80] ; (3) H. pylori-induced production of free radicals [80][81][82] , cytotoxins and cytokines [57][58][59][60][61]78] , which may also result in blood-brain barrier disruption; (4) changes in neurotransmitter secretion in gastric mucosa and spinal cord [56,72,75,81,[83][84][85] ; (5) neuron injury resulting from gastric mucosa atrophy and a decrease in vitamin B12 absorption [86] ; and (6) changes in stomach and intestinal microbiota [6,[87][88][89] .…”
Section: Role Of the Brain-gut Axis In Acute H Pylori Infectionmentioning
confidence: 99%
“…Intermediate effects of chronic H. pylori infection on brain-gut axis function have been clinically observed as: (1) the alteration of feeding patterns [15,19] ; (2) cognitive and memory dysfunction [18,19,27,82,93] , increased vulnerability to stress [15,19,27] and anxiety-and depressive-like behaviors [19] ; (3) alterations in endocrine functions of the stomach, including the production of SP, VIP, CCK, STS, gastrin and ghrelin [81,94] ; (4) changes in visceral ANS balance and the action of vagal visceral reflexes [95] ; (5) alterations in gastrointestinal motility [21] ; (6) increased visceral perception (chemo-and mechano-hypersensitivity) [67,96] ; (7) changes in gastrointestinal secretion [21,45] ; (8) increased intestinal permeability [23,61] ; (9) intestinal microbiota [87][88][89] , with indirect effects on the brain-gut axis [27,28,[97][98][99] ; (10) alterations in immunological reactivity, resulting in decreased prevalence of food allergies and inflammatory bowel diseases [46,100] ; and (11) the overlapping of gastrointestinal disorders from upper and lower parts of the digestive tract [43] . Moreover, H. pylori eradication has also been shown to normalize some of these alterations [55,95,[100][101][102][103] .…”
Section: Role Of the Brain-gut Axis In Chronic H Pylori Infectionmentioning
confidence: 99%
“…In gastric mucosa ghrelin administration reduces the damage evoked by ethanol, alendronate, oxidative stress (OS), gastric resection, acetic acid, diabetic inflammation and ischemia-reperfusion (I/R) state 55 . El Eter et al 56 have reported an antioxidant effect of ghrelin in the gut by increasing nitric oxide (NO) release, leading to reduce ulceration, tissue congestion and increase vascular permeability and cellular infiltration.…”
Section: Effects Of Ghrelin In the Gutmentioning
confidence: 99%
“…Among the major symptoms of FD, postprandial fullness as well as epigastric pain, epigastric burning, and early satiation should be "bothersome." An investigation on the effect of meal ingestion on symptom generation indicated that not only postprandial fullness and early satiety but also epigastric pain, an epigastric burning sensation, and nausea (not vomiting) may increase after meals [50]. H. pylori infection is considered a possible cause of dyspepsia if successful eradication leads to a sustained resolution of symptoms for more than 6 months, and such status can be termed HpD [52].…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, our group summarized the data of the Rikkunshito study and focused on the difference between tertiary care hospitals and primary clinics [49]. Using the dataset of the previously performed randomized placebo-controlled trial to evaluate the efficacy of rikkunshito, a Japanese herbal medicine, in patients with FD [49], they evaluated the predictive markers of the efficacy of rikkunshito and found that a low baseline plasma des-acyl ghrelin level [50] was associated with an increased treatment efficacy of rikkunshito against FD, but the same finding was not reported by the intervention sites (tertiary hospitals or primary clinics) [51].…”
Section: Core Symposium 3 Of the 13th Annual Meeting Of The Jga (2017)mentioning
confidence: 99%